Rising temperature accelerates the responses of inducible anti-predator morphological defenses of Ceriodaphnia cornuta but decreases the responsive intensity - Shanshan Qin (Elsevier, 2021)
Cladocerans can recognize predation risk by sensing the chemical cues released by their predators, and adopt effective anti-predator defensive strategies to avoid being predated. In nature waters, temperature, as one of the key abiotic factors, fluctuates with day-night and seasons, especially under climate warming, which may impact the inducible anti-predator defenses of cladocerans. To investigate the effects of rising temperatures on the inducible anti-predator defenses of cladocerans, we cultured a common species Ceriodaphnia cornuta at presence or absence of Chaoborus sp. larvae kairomone at 15, 20, 25, and 30 °C for 15 days. Results showed that both the inducible anti-predator morphological responses and all the life history traits of C. cornuta were significantly affected by temperature changes. Specifically, rising temperature accelerated the inducible defense responses of the horn formation, but reduced the expression intensity of this morphological defense trait. With increasing temperature, the body size was increased, the time to first reproduction was decreased, and the reproduction was enhanced, indicating that C. cornuta tends to adopt K-selective strategy with maturity at relatively larger size and r-selective strategy with relatively earlier reproductive time and more offspring under warming conditions. These data demonstrated that the inducible anti-predator responses and the life history traits of C. cornuta can be shifted by temperature changes, which may indirectly affect top-down species interactions. Our study highlights the importance of incorporating species interactions when estimating the impact of rising temperature on species.